Divine Simplicity and the Boundaries of Orthodoxy - Harwood, Adam (Religions, 2024)
This paper explores whether the classical view of Divine Simplicity (DS) is required to remain in the bounds of Christian orthodoxy. After defining key terms, a method is proposed and employed for identifying the boundaries of orthodoxy: searching the statements of the four ecumenical councils for explicit affirmations of DS. In addition, three historic confessions and a significant contemporary statement of faith are examined for affirmations of the classical view of DS. The conclusion is that an affirmation of the classical view of DS is orthodox, but not required for orthodoxy.